Coaching on Borrowed Time: Balancing the Roles of the Literacy Professional. (31st October 2018) - Pletcher, Bethanie C.; Hudson, Alida K.; John, Lini; Scott, Alison
Abstract: Serving both teachers and students in a hybrid literacy professional role requires thoughtful planning and reflection. In this article, the authors reflect on their work over the course of one school year to determine how to manage time effectively to combine the job descriptions of reading specialist and literacy coach. Strategies are presented for each of the following topics that emerged as a result of these reflections: sticking to a schedule while remaining flexible, seeking topic choices that balance different needs, starting small by coaching a few teachers at a time, using expert teachers, holding brief but effective coaching conversations, and seeking support for coaching.